Livedo Reticularis during Amantadine Treatment. Issue 5762 (12th June 1971) - Vollum, Dorothy I.; Parkes, J. D.; Doyle, D.
Abstract : Livedo reticularis is a common side effect of treatment with amantadine for Parkinson's disease. Investigation of 40 such patients suggests that the livedo is a physiological response provoked by depletion of catecholamine stores in peripheral nerve terminals.